2014
DOI: 10.1021/cg500512e
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions and Second-Harmonic Generation Properties of (E)-1,5-Diarylpentenyn-1-ones

Abstract: Investigation of crystal structures of eight quasi-planar (E)-1,5-diarylpentenyn-1-ones has been carried out. Five of these compounds crystallize in chiral space groups. Intermolecular interactions responsible for the loss of planarity and steric hindrances that prevent molecules to form centrosymmetric dimers were suggested to be the reasons of the crystallization in chiral groups. Intermolecular bonding has been investigated by means of the Hirshfeld surfaces, and the role of the C–H···O interactions as driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…The most expected positions of acceptors of hydrogen bonding for the chalcone are situated on the opposite sites of the molecule, and correlate well with observed supramolecular synthons in its polymorphs-a dimer depicted in Figure 10, a {BZYACO01}and a head-to-tail chain {BZYACO04} similar with that of 5-(4-bromophenyl)-1-phenylpent-2-en-4-yn-1-one. Elongation of the π-conjugated chain with a triple bond makes the appearance of such chains more abundant than dimer occurrence (Figure 10b), that was experimentally confirmed for a series of 1,5-diarylpent-2-en-4-yn-1-ones [246,247]. This tool has been applied mainly for the analysis of strong hydrogen bonds [54,170,190,194,[248][249][250][251] in accord with the first test functional groups suggested within this tool, and the first paper published to describe it.…”
Section: Full Interaction Mapsmentioning
confidence: 56%
“…The most expected positions of acceptors of hydrogen bonding for the chalcone are situated on the opposite sites of the molecule, and correlate well with observed supramolecular synthons in its polymorphs-a dimer depicted in Figure 10, a {BZYACO01}and a head-to-tail chain {BZYACO04} similar with that of 5-(4-bromophenyl)-1-phenylpent-2-en-4-yn-1-one. Elongation of the π-conjugated chain with a triple bond makes the appearance of such chains more abundant than dimer occurrence (Figure 10b), that was experimentally confirmed for a series of 1,5-diarylpent-2-en-4-yn-1-ones [246,247]. This tool has been applied mainly for the analysis of strong hydrogen bonds [54,170,190,194,[248][249][250][251] in accord with the first test functional groups suggested within this tool, and the first paper published to describe it.…”
Section: Full Interaction Mapsmentioning
confidence: 56%
“…As the independent molecules of ketone 2 have similar conformations, their crystalline environment becomes of particular interest because it can rationalize why Z 6 ¼ 1. Previously, we found that the most abundant C-HÁ Á ÁObonded associates in the crystals of chalcones, polyenones and pentenynones include dimers, head-to-tail chains and zigzag C-HÁ Á ÁO chains with the most acidic proton of a molecule (Vologzhanina et al, 2014). The two independent molecules of ketone 2 demonstrate two of these motifs ( Fig.…”
Section: Supramolecular Featuresmentioning
confidence: 84%
“…Both trans-cis isomerization and [2 + 2] cycloaddition reactions can be observed depending on the nature of the substituents on the alkyl chain (Vatsadze et al, 2006). Many of the compounds previously reported by us, including 1,5-diarylpentenynones (Golovanov et al, 2013;Vologzhanina et al, 2014;Voronova et al, 20161) and cyclic ketones with vinylacetylene fragments (Voronova et al, 2018) in crystals exhibit coplanar packing with a distance between the olefin fragments of less than 4.2 Å ; thus, they satisfy the Schmidt (1971) criteria for a solidstate [2 + 2] cycloaddition to occur. However, our numerous attepts to carry out [2 + 2] photocycloaddition in these compounds were unsuccessful.…”
Section: Chemical Contextmentioning
confidence: 97%
“…FIMs at (top) 3b and (bottom) 3d probed with CÁ Á ÁBr interactions. carbonyl group are screened by aryl substituents, so that the head-to-tail chains typical for closely related 1,5-diarylpentenynones (Vologzhanina et al, 2014;Voronova et al, 2016) become less favourable. The tert-butyl groups connected to the cyclohexane ring are able to take part in C-HÁ Á ÁO hydrogen bonding in agreement with the FIMs.…”
Section: Figurementioning
confidence: 99%
“…The latter requires a compound not only to exhibit second harmonic generation properties, but also to crystallize in an acentric space group. Recently, we reported that modification of chalcones with aryl/heteroaryl-allyl groups destabilizes the centrosymmetric C-HÁ Á ÁO-connected dimer motifs widespread among chalcones, so that numerous pentenynones tend to crystallize in acentric and chiral space groups and exhibit second harmonic generation properties (Vologzhanina et al, 2014;Voronova et al, 2016). As crystalline second-order nonlinear susceptibility depends also on the molecular dipole moment, we assumed that modification of pentenynones to bis(arylallylmethylidene)alkenones should both destabilize dimer motifs and give a convenient pathway ISSN 2053ISSN -2296 # 2018 International Union of Crystallography for varying the molecular dipole moment.…”
Section: Introductionmentioning
confidence: 99%